Recent years status of sediment bed of Golden Horn (Istanbul) after year 1999 - Gonullu, M. Talha; Avsar, Yasar; Apaydin, Omer; Bayhan, Hurrem; Kurt, Ugur (SPRINGER, 2006)
Golden Horn is an estuary in Istanbul. It has connection with Marmara Sea directly and with Black Sea via Bosphorus, and was polluted by different kinds of industrial plants up to 1999. In addition to this, municipal wastewater of around one million people has been discharged to here. Greater part of the estuary was almost blocked off by sediment islands. Extensive effort was spent to dredge sediment in 1999. This created quite a convenient condition for aquatic medium in the estuary. In this research, the variations of chemical compositions of sediment bed were investigated to get clue about ecological conditions of the estuary. For that purpose, sediment samples were taken from 6 stations along the estuary in 2001, 2003 and 2004. The sediment samples were analyzed for inorganic and organic constituents. Meanwhile, water samples (from the surface and just above benthic mass) were also taken from the same 6 places and they were analyzed to verify the data from sediment samples. By this way, correlations between sediment mass and water body were determined.
Keywords: Istanbul; Golden Horn; sediment; organic content; SOD-B; SOD-C; DO; OXYGEN-DEMAND; Environmental Sciences & Ecology